Selfie glitch exposing the glitch in virtual identities - De Leos, Darshelle Andiella P.; Romero, Riza; Malto, Marco Ruben T. II (Quezon City College of Fine Arts, University of the Philippines Diliman, 2018)
My work and experiences led me to investigate the significance of transparency towards the public with regards to what we display about online. My work aims to highlight the inauthenticity of the virtual self by using objects such as the bed, a projection mapping of glitches and a 'logged in' sign as visual metaphors that represent one's virtual identity. The study seeks to expose our dependence towards social media and how we have framed our measure of acceptance, stress, and happiness to it, so much so that our susceptibility is almost sure. As a former style blogger and as an active social media user, I am using my own experiences and observations as a reference point. From those experiences, I came to the realization that, in one way or another, there is a discrepancy or a glitch in how we all present ourselves in social media. With this in mind, practical research was done to assess that this plight that I call "glitch" in real and virtual identities could lead to emotional and psychological distress such as anxiety and depression
Thesis (Bachelor of Fine Arts - Painting)--University of the Philippines Diliman
Bibliography : leaves 18-20.
Keywords: Self-presentation in art; Installations (Art)